STRUKTUR KOMUNITAS ZOOPLANKTON DI KOLAM RETENSI KAMBANG IWAK PALEMBANG - Yulisa, Yulisa; Mutiara, Dian (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2016)
Research of Â zooplankton community structure in a retention pond Kambang Iwak Palembang was held in May 2016 until June 2016 in the retention pond Kambang Iwak Palembang, aims to determine the community structure of zooplankton. Â Zooplankton samples were taken from five stations. Subsequently the samples were identified and analyzed include abundance, dominance and diversity index. Results showed that the composition of zooplankton in the retention pond Kambang Iwak Palembang City composed of 10 species are Astasia sp, Cyclops sp, Moina weismenni, Scopholeheris mucronala, Philodina sp, Retatoria, Alona sp, Branchionus falcatus, Daphnia pulex, Leptodora sp. Abundance highest total in five stations owned by Cyclops sp species, amounting to 9.38 ind / l. The highest dominance index has a value of 0.29, so it can be said there is no species that dominate the waters of the lake. Diversity of zooplankton in five stations categorized as Low to Medium with a diversity index of between 0.86 to 1.41Keywords : zooplankton, retention pondABSTRAKÂ Penelitian tentang struktur komunitas zooplankton di kolam retensi Kambang Iwak Kota Palembang telah dilaksanakan pada bulan MeiÂ  sampai Juni 2016 di kolam retensi Kambang Iwak Kota Palembang, untuk mengetahui struktur komunitas zooplankton yang terdapat di sana. Sampel zooplankton diambil dari lima stasiun , selanjutnya diidentifikasi dan dianalisis meliputi kelimpahan, dominansi, dan indeks keanekaragamannya. Hasil Penelitihan menunjukkan bahwa komposisi zooplankton di kolam retensi Kambang Iwak Kota Palembang terdiri dari 10 spesies, yaitu Astasia sp, Cyclops sp, Moina weismenni, Scopholeheris mucronala, Philodina sp, Retatoria, Alona sp, Branchionus falcatus, Daphnia pulex, Leptodora sp. Kelimpahan total di limaÂ  stasiun tertinggi dimiliki oleh species Cyclops sp, sebesar 9,38 ind/l. Indeks dominansi tertinggi memiliki nilai 0,29, sehingga dapat dikatakan tidak ada species yang mendominasi perairan danau. Keanekaragaman zooplankton di lima stasiun dikategorikan Rendah sampai Sedang dengan indeks keanekaragaman antara 0,86 â 1,41Kata kunci : zooplankton, kolam retensi